Palm Walk, Botanic Gardens, Port-of-Spain, Trinidad - (:unkn) unknown (Ye Adamson Printerie, Port of Spain, Trinidad, 2010)
The postcard shows palms along the pathway in the botanical gardens.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Plants--Trinidad and Tobago; Garden walks--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Gardens--Trinidad and Tobago; [1910]